Evaluasi Discrepancy Program Pengelolaan Sampah dan Limbah dalam Meningkatkan Kesadaran Lingkungan - Alfiyyatur Rohmaniyyah, Ummi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Waste management in Islamic boarding schools (pesantren) possesses unique characteristics by integrating spiritual values with environmental sustainability practices. Pesantren serve not only as centers of religious education but also as agents of change in promoting environmental awareness. This study aims to evaluate the waste and garbage management program at Al-Imdad Islamic Boarding School, Yogyakarta, in fostering students' environmental awareness using the Discrepancy Evaluation Model (DEM). This research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation analysis. The results indicate that the program has undergone five stages of evaluation: design, installation, process, product, and cost-benefit analysis. The program shows effectiveness in the design, installation, and product stages; however, a gap remains in the cost-benefit analysis stage, particularly in funding and program sustainability. The implications of this study provide valuable insights for pesantren administrators and policymakers to develop more systematic, participatory, and Islamic value-based waste management programs that align with sustainable development goals